Invasive African clawed frogs (Xenopus laevis) in Washington State: status, response efforts, and lessons learned - Emmenegger, Eveline J.; Lavier, Rebecca A.; Struck, Emily J.; Tyurina, Vasilisa P.; Eskew, Evan A.; Friesen, Megan R.; Taylor, Mark A.; Bueren, Emma K.; Kyle, David R.; Schultz, Jesse M.; Pleus, Allen; Visser, Richard H.; et al. (Frontiers in Amphibian and Reptile Science, 2025)
The African clawed frog (ACF, Xenopus laevis), which is indigenous to sub-Saharan Africa, is an aquatic invasive species known to have severe ecological impacts on native fauna when introduced into non-endemic regions. In 2015, ACFs were detected in Washington State, U.S. for the first time, and the species is now documented at three cities across western Washington: Lacey, Bothell, and Issaquah. We cataloged the known ACF occurrences, early management efforts, biological data about the frogs, and status of these invasive populations at the three sites from 2015–2023. The ACFs appear to be established in at least three watersheds in the Puget Sound region despite substantial effort at eradicating them at one site. Presence of ACFs in watersheds that lack surface connectivity implies independent introduction events, and the capture of frogs in multiple subbasins in the same watershed may reflect the potential for further spread. Because the ACF is nocturnal and otherwise behaviorally and visually highly cryptic, other established populations may go undetected. Where the ACFs are largely confined to stormwater ponds — as many of our current observations suggest — eradication may still be possible, though a substantial, focused effort would be required. In addition, significant refinement of eradication approaches will be needed to ensure effectiveness in topographically and vegetatively complex Pacific Northwest aquatic environments.